Development and techno-economic analysis of an integrated petroleum coke, biomass, and natural gas polygeneration process. (15th October 2016) - Salkuyeh, Yaser Khojasteh; Elkamel, Ali; Thé, Jesse; Fowler, Michael
Abstract: This work presents the techno-economic analysis results of a novel polygeneration process that converts biomass, petcoke, and natural gas into methanol, ethanol, DME, olefins, FT-liquids, and electricity, while eliminating CO2 emissions. A comprehensive process simulation model was developed in Aspen Plus. The economic optimization of the plant is performed for a wide range of biomass to petcoke ratios: 0%, 5%, 10%, and 20%, using the particle swarm optimization technique. Moreover, five different optimization scenarios are considered for each feedstock including maximizing profitability of the plant, maximizing petcoke utilization, maximizing fuel production, maximizing olefin production and maximizing ethanol production. The economic optimization results showed that up to 65% of feedstock inlet can be a petcoke/biomass mixture while the process is still profitable. In addition, the results indicate that the methanol scenario leads to the minimum thermal efficiency and NPV compared to the other chemical production units. Highlights: Development of an integrated natural gas reforming and petcoke-biomass gasification. Ethanol production from petcoke and biomass. Polygeneration process with zero direct carbon emissions.